The Effect OF Teacher's Professional Competence on Student’s Entrepreneurship Competency in Practice and Entrepreneurship Lessons at SMKN 1 Solok (A Social Science and Entrepreneurship Journal, 2023)
The purpose of this study was to determine the effect ofteacher professional competence on studententrepreneurship competence in the subjects of craft andentrepreneurship at SMKN 1 Solok, in this study using aquantitative approach, the data sources used in this studywere primary data and secondary data, primary data namelydata which is directly obtained from respondents from fillingout google forms , while secondary data comes fromliterature studies in the form of journals, books and lawsrelated to research. The result of the research is that theprofessional competence of teachers has a positive effect onthe entrepreneurial competence of students at SMKN 1Solok .
Keywords: Teacher’s Professional; Competence; Student Entrepreneurship Competence.